ANALYSIS OF PRICING STRATEGY IN INTERNATIONAL MARKETING - Resti Hardini; Rahayu Lestari; Suadi Sapta Putra; Kumba Digdowiseiso; Azizul Yadi Yaakop (RADJA PUBLIKA, 2024)
In-depth pricing strategies in international marketing are examined in this literature review in an effort to provide a thorough understanding of the theory, impact, and conceptual framework. The background of the research emphasizes how complex international markets are and how pricing strategies must be modified to account for trade regulations, cultural variances, and market dynamics. By examining the theories of elasticity of demand, purchasing power parity, market penetration, and price differentiation, this research methodology employs a methodical literature review approach. The findings indicate that striking the correct balance between these factors is necessary for a successful pricing strategy. Demand elasticity is essential for adapting prices to the market, and relative price adjustments are guided by purchasing power parity. While price differentiation works well for high-quality products, market penetration strategies can also be beneficial in gaining market share. The talk focuses on the opportunities and new challenges that come with putting this strategy into practice. The study's conclusion highlights the significance of having a thorough understanding of environmental theories and variables when putting responsive pricing strategies into practice in global marketplaces. The ability of the business to consistently adjust to shifting global dynamics is just as important to its success as determining the appropriate prices.